Application of Functional Ice (FICE) to Reduce the Incidence of Spoilage Microorganisms on the Surface of Shrimp, Tilapia, and Chicken - Wú A., Bet S. (Zamorano: Escuela Agrícola Panamericana, 2020., 2020)
This research project's focus was to devise a method to reduce food waste, a straightforward and innovative way to increase both the safety and shelf life of raw animal foods. To reduce spoilage and improve the quality of seafood and poultry during storage and transportation; we proposed to develop a “Functional Ice” (FICE). FICE cubes was manufactured with acid peracetic (PAA) in concentrations of 0, 50, 100, 150, 200 and 300 ppm. Seafood (shrimps and whole eviscerated tilapia and chicken parts (drumsticks) were stored on FICE to simulate transport and storage conditions during 24 (seafood) and 48 hours (chicken parts). Samples analyzed for spoilage microflora counts considered aerobic plate count, Enterobacteriaceae, total coliforms, Escherichia coli (E coli), and lactic acid bacteria. Chicken samples' physicochemical parameters (pH, temperature, and L*, a*, b* color) and seafood samples' sensorial parameters (texture, odor, color, taste, and overall acceptance) were evaluated. Samples stored with PAA at 150 - 300 ppm showed significantly lower APC (2 - 2.5 log CFU/g), total coliforms, E. coli, and lactic acid bacteria (1 - 2 log CFU/g) compared to the control treatments. FICE storage reduced the incidence of these microorganisms. Findings provide a simple and innovative approach for shrimp, tilapia, and poultry processors in Honduras to minimize spoilage, preserve meat quality, and reduce food losses without significant investments.